The spiritual significance of glaciers in an age of climate change. (10th August 2015) - Allison, Elizabeth A.
<x xml:space="preserve">Abstract</x> Climate change has largely been understood as a biophysical, economic, and political phenomenon. This approach has obscured the ways in which climate change also poses a challenge to human subjective understandings of self and society in relation to place, and in relation to perceptions of the sacred. Glaciers, as dominant features of high mountain landscapes, are sites of easily observable consequences of climate change, grounding the consequences of distant carbon emissions in material surroundings. They are also sites of powerful sacred and symbolic meanings for local communities. This review examines three instances of glacial decline in sacred mountain landscapes, in the Peruvian Andes, the Nepalese Himalaya, and the Meili Snow Mountains of Yunnan, China. These examples show that glacial decline is not simply a material process, but also has important implications for the ways that local people understand themselves and make meaning in relation to their surroundings. Locally grounded values arising from particular experiences of the landscape, especially from those most at risk from effects of climate change, may offer new avenues of ethical reflection around climate change that can and should influence larger climate discourses. WIREs Clim Change 2015, 6:493–508. doi: 10.1002/wcc.354 For further resources related to this article, please visit the WIREs website.